A Critique of Jean-Paul Sartre's Ontology - Natanson, M.A. author. aut Link
VIII, 142 p.
Keywords: "Why is my pain perpetual, and my wound incurable, which refuseth to be healed?" -Jeremiah "Existentialism" today refers to faddism, decadentism, morbidity, the "philosophy of the graveyard"; to words like fear, dread, anxiety, anguish, suffering, aloneness, death; to novelists such as Jean-Paul Sartre, Dostoievski, Camus, Kafka; to philosophers like Kierkegaard, Heidegger, Marcel, Jaspers, and Sartre-and because it refers to, and is concerned with, all of these ideas and persons, existentialism has lost any clearer meaning it may have originally possessed. Because it has so many definitions, it can no longer be defined. As Sartre writes: "Most people who use the word existentialism would be em barrased if they had to explain it, since, now that the word is all the rage, even the work of a musician or painter is being called existentialist. A gossip columnist . . . signs himself The Exis tentialist, so that by this time the word has been so stretched and has taken on so broad a meaning, that it no longer means anything at all. " 2 This state of definitional confusion is not an accidental or negligible matter. An attempt will be made in this introduction to account for the confustion and to show why any definition of existentialism in volves us in a tangle. First, however, it is necessary to state in a tenta tive and very general manner what points of view are here intended when reference is made to existentialism.